The Foreign Direct Investment (FDI) of Korea in Vietnam from the Perspective of Economic Security - Nhung, Vu Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 3, 2018)
Korea is now the largest investor in Vietnam with billion-dollar foreign direct investment (FDI) projects. Korea’s investment is a “phenomenon” in attracting FDI in Vietnam either. In addition to their undeniably positive effects, the Korean FDI activities in Vietnam have unique characteristics that have posed complex economic security-related issues. There have been so far many studies on Korean FDI activities in Vietnam, but few have examined how they affect Vietnam’s economic safety, stability and sustainability from the perspective of economic security, so as to provide a comprehensive view on their effect. By reviewing Korean FDI activities in Vietnam over the past few years, this article indicates what the Korean FDI activities look like from the perspective of economic security and proposes accordingly key solutions and policy recommendations in improving the quality and efficiency of Korean FDI activities towards sustainable development in Vietnam in the years to come.